2020
DOI: 10.1016/j.pep.2019.105510
|View full text |Cite
|
Sign up to set email alerts
|

Design, production and purification of a novel recombinant gonadotropin-releasing hormone associated peptide as a spawning inducing agent for fish

Abstract: GnRH is a neuropeptide known to regulate reproduction in vertebrates. The purpose of this study was to design and produce recombinant gonadotropin-releasing hormone associated peptide (rGnRH/GAP) as an alternative of the previous GnRHs and native extracted hormone from tissue, to induce final maturation in fish. Decapeptide as well as GAP area sequences were compared between GnRH1, GnRH2, and mGnRH from Acipenser sp and Huso huso, respectively. Considering the conserved amino acids and the replacement of unsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…These results agree with those reported for sex‐reversed Nile tilapia ( Oreochromis niloticus ) (Phumyu et al., 2012). Additionally, applications of steroid hormones can trigger increases in red blood cell, haematocrit and haemoglobin values (Ma et al., 2020; Mohammadzadeh et al., 2020). The current study also reported the serum biochemical values of sex‐reversed female rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those reported for sex‐reversed Nile tilapia ( Oreochromis niloticus ) (Phumyu et al., 2012). Additionally, applications of steroid hormones can trigger increases in red blood cell, haematocrit and haemoglobin values (Ma et al., 2020; Mohammadzadeh et al., 2020). The current study also reported the serum biochemical values of sex‐reversed female rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the column was washed with 10 bed volumes by washing buffer (50 mM Tris, 300 mM NaCl, 10 mM Imidazole and 0.05% Triton x-100 at pH 8.0). Finally, the His-tagged protein was eluted with 5 bed volumes elution buffer (50 mM Tris, 150 mM Imidazole and 1% (v/v) Triton x-100, pH 7.5) at a flow rate of 1 mL min -1 and before molecular characterization (Mohammadzadeh et al, 2020). rGnRH quantity was determined by Bradford's method (1976) with bovine serum albumin as a standard.…”
Section: Production Of Recombinant Gnrhmentioning
confidence: 99%
“…Apparently, a reliable, more effective, available and cheap product, useful to induce the final maturation, is required (Aizen et al, 2017). Therefore, recombinant protein methods are used instead of synthetic production for managing the costs (Mohammadzadeh et al, 2020). The potential for the generation of recombinant hormones has been achieved in recent years due to recent advances in construction cDNA encoding target protein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations